Moderating Effect of Smartphone Use Between Loneliness and Bedtime Procrastination Among Adolescents - Pucyutan, Job (Journal of Interdisciplinary Perspectives, 2025)
This study investigated whether smartphone use moderated the relationship between loneliness and bedtime procrastination among adolescents. Using a quantitative research design, data were gathered from 202 students aged 12 to 19 in public and private schools in Tanauan City, Batangas, through simple random sampling. Standardized tools were utilized: the De Jong Gierveld Loneliness Scale for emotional (α = .67 to .74) and social loneliness (α = .70 to .73), the Bedtime Procrastination Scale (α = .92), and the Smartphone Use Scale (α = .71). Statistical methods such as mean, standard deviation, Pearson correlation, and moderation analysis using Hayes' Process Macro were employed to analyze the data. The results showed that the respondents experienced both emotional and social loneliness, alongside a slightly elevated level of bedtime procrastination and moderate smartphone use. A significant relationship was found between social loneliness and emotional loneliness and bedtime procrastination, with r-values of .311 and .321, respectively, and p-values of .000, indicating a low but positive correlation. This suggested that higher levels of loneliness were associated with increased bedtime procrastination among adolescents. However, smartphone use was not found to significantly moderate this relationship, as indicated by the results of the moderation analysis [B = -0.021, F(1, 198) = 30.454, p = 0.726]. Thus, the effect of loneliness on bedtime procrastination remained consistent regardless of the level of smartphone use. These results suggest that interventions targeting adolescents’ emotional and social well-being, by fostering meaningful social connections, promoting self-regulation, and encouraging balanced smartphone use, may be more effective in reducing bedtime procrastination than strategies focused solely on technology use. Based on these findings, a program was proposed to help reduce feelings of loneliness, manage bedtime procrastination, and encourage healthier smartphone habits among adolescents.